Failure Dependence Of Semiconductor Devices On Low Temperatures - Salem, M. R.; Talat, L. A. (Al-Mukhtar Journal of Sciences, 1998)
The paper studies the effect of low temperatures on the failure of power semiconductor devices. Due to the high difference of thermal coefficient between the silicon wafer and dilatation electrodes, and in some cases in the solder connecting both ; a high mechanical stress occurs and results cracks in the intermediate layers. These cracks produce big change in the reverse I -V characteristic for some devices and finally an electrical failure occurs. There are different methods used for location of failure, this study uses a simple method based on mechanical stability of the system. Different sets were chosen randomly from different groups of production. The samples were put in the cryostat and the temperature was adjusted from 0 °C to - 196 °C to determine the failure sample and its corresponding temperature. The data collected experimentally was analyzed using probability density function and cumulative probability distribution function. The results indicate that there are a strong correlation between the critical temperature and the type, construction of system as well as the quality of the technological processes during the manufacturing of semiconductor devices.